Adsorption of groundwater As(V) on chitosan-coated bentonite batch and fixed-bed studies - Arida, Carlo Vic J. (2013)
Batch and fixed-bed experiments were conducted to understand the mechanism and kinetics of groundwater As(V) adsorption on chitosan-coated bentonite (CCB). The Freundlich isotherm (R² = 0.924) and pseudo-second order kinetic model (R² = 0.995) best describe batch adsorption of groundwater As(V) onto CCB. Thermodynamic study showed that As(V) adsorption is spontaneous and endothermic. An increase in randomness of the CCB-solution interface occurs during the adsorption process. Batch studies agreed that the As(V) adsorption on CCB is chemisorptions. Fourier transform infrared (FTIR) analysis shows that both the ?OH and -NH₂ functional groups of chitosan are responsible for the As(V) adsorption. Ions present in groundwater affect the As(V) adsorption on CCB. Initial concentration (Co: 100-500 µg/L), adsorbent mass (m: 6.0-8.0 g) and flow rate (Q: 0.6-1.0 mL/min) on As(V) removal were analyzed using Box-Behnken design. Optimum process conditions (Co = 418.12 µg/L, m = 6.6 g and Q = 0.65 mL/min) resulted in a maximum breakthrough time of 216.15 min and As(V) uptake capacity at breakthrough point of 10.57 µg As(V)/g CCB. The breakthrough curve from the optimum condition fits the Hutchins Bed Depth Service Time (BDST), Thomas and Yoon-Nelson models with the same R² values of 0.95. However, Yoon-Nelson best describes the groundwater As(V) adsorption on CCB in a fixed-bed column system. The results of this study will serve as a tool in the design of permeable reactive barriers (PRB) in treating As(V) contaminated groundwater.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman
Keywords: Adsorption